Quarantine as a possibility: A phenomenological essay on freedom in confinement times - Salomón Paredes, Alejandro Khaled (2020)
This essay describes the quarantine experience from a psychological and existential perspective in the first person, with an investigative position supported by existential analysis and logotherapy, which explores, among other things, the experience of lack of meaning, attitudes towa rds the adverse situation, the emotions that are experienced, the margin of freedom and responsibility in the face of the circumstance, as well as the possibilities of realization of values that the quarantine offers, resorting to the anthropology of Viktor Frankl and authors such as Scheler, Kierkegaard, Jaspers , Heidegger, Buber, among others.